2016
DOI: 10.1016/j.jid.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

One SNP at a Time: Moving beyond GWAS in Psoriasis

Abstract: Although genome-wide association studies have revealed important insights into the global genetic basis of psoriasis, the findings require further investigation. At present, the known genetic risk loci are largely uncharacterized in terms of the variant or gene responsible for the association, the biological pathway involved, and the main cell type driving the pathology. This review primarily focuses on current approaches toward gaining a complete understanding of how these known genetic loci contribute to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 91 publications
0
58
0
3
Order By: Relevance
“…SNP was a classical topic of research which indicated a variation in a single nucleotide that occurs at a specific position in the genome [15]. And with the development of research, especially the studies on miRNA, the SNPs in the 3′UTR region which were targets of miRNA have been shown in many studies to affect the binding of miRNA to cause "Gain" and "Loss" regulation of certain miRNAs [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…SNP was a classical topic of research which indicated a variation in a single nucleotide that occurs at a specific position in the genome [15]. And with the development of research, especially the studies on miRNA, the SNPs in the 3′UTR region which were targets of miRNA have been shown in many studies to affect the binding of miRNA to cause "Gain" and "Loss" regulation of certain miRNAs [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have identified 40 loci in patients with psoriasis, many of which are related to immune function, including the endoplasmic reticulum aminopeptidase 1 (ERAP1), whose product is relevant to peptides binding to the MHC class I molecules, especially HLA-C*0602 and HLA-B*27 46 . SNPs related to genes relevant to immune function include loci containing genes involved in nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling ( REL , TNF α-induced protein 3-interacting protein 1 [ TNIP1 ], NF-kB inhibitor alpha [ NFKBIA ], and caspase recruitment domain family member 14 [ CARD14 ]), interferon (IFN) signaling (interleukin 28 receptor A [ IL-28RA ] and tyrosine kinase 2 [ TYK2 ]), T-cell regulation (Runt-related transcription factor 3 [ RUNX3 ], interleukin 13 [ IL-13 ], T-cell activation RhoGTPase activating protein [ TAGAP ], ever shorter telomeres protein 1 [ ETS1 ], and methyl-CpG binding domain protein 2 [ MBD2 ]), antiviral signaling (IFN-induced helicase C1 protein [‎ IFIH1 ], DEXD/H-box helicase 58 [ DDX58 ], and ring finger protein 114 [ RNF114 ]), and genes involved in the IL-23 pathway which specifically implicate a role for Th17 cells ( TNFAIP3 , IL-23R , IL-12B , TNF receptor associated factor 3 interacting protein 2 [ TRAF3IP2 ], IL-23A , and signal transducer and activator of transcription 3 [ STAT3 ]).…”
Section: What Have We Learnt About the Pathogenesis Of Psoriatic Arthmentioning
confidence: 99%
“…Genetic markers are variants in the human genome that are (alone or in combination) associated with a specific disease phenotype . A variation may have functional consequences, such as altering the expression or function of a gene that directly leads to disease, or may have no direct functional result at all . Genetic markers would be useful as diagnostic tools to identify high‐risk patients or predictors of prognosis or response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs, or variants at a single DNA base pair) have received much attention as potential genetic markers. SNPs have the advantage of being present at a high frequency in the human genome and can be genotyped easily and inexpensively using standard techniques …”
Section: Introductionmentioning
confidence: 99%